Resilient futures: Acknowledging the shared challenges of early career food system researchers in uncertain times - Boylan, Sinead; Manohar, Swetha; Ambikapathi, Ramya; Fabila, Max; Cubillo, Beau; Mauli, Senoveva; Lukanga, Editrudith; Oloko, Ayodele; Fanzo, Jessica (Elsevier, 2026)
Transforming food systems to deliver sustainable, equitable, and nutritious outcomes requires confronting profound global challenges, from climate change and biodiversity loss to widening inequities and persistent malnutrition. Early career researchers (ECRs), who make up a large proportion of the research workforce, hold unique potential to drive this transformation through fresh perspectives, systems thinking, and transdisciplinary collaboration. Yet they also face distinct barriers: precarious employment, limited funding, and institutional structures that privilege dominant knowledge systems, while undervaluing Indigenous and community-centred approaches. For many, particularly in resource-constrained or Indigenous contexts, these professional pressures are compounded by structural inequities, colonial legacies, and personal responsibilities, amplifying the emotional burden of engaging with such complex challenges. This paper explores strategies to empower ECRs to navigate food systems research without becoming overwhelmed. We highlight the importance of adaptability, mentorship, and building supportive networks, alongside recognition of Indigenous knowledge systems and the contextual realities shaping food systems across geographies. Collaboration and co-production emerge as critical pathways for innovation, trust-building, and collective action, while diverse outputs beyond peer-reviewed publications are essential to translate research into meaningful policy and practice. By embracing persistence, equity, and shared responsibility, ECRs can position themselves not as isolated individuals but as key actors in a global movement for resilient and just food systems. Balancing realism with optimism, we reaffirm the transformative potential of ECRs, and call on institutions, funders, and senior researchers to establish structures that enable them to thrive as changemakers in pursuit of a sustainable food future.